A Systematic Review of Artificial Intelligence in Assistive Technology for People with Visual Impairment - Triyono, Liliek; Gernowo, Rahmat; Prayitno; Cholil, Saifur Rohman (Universitas Muhammadiyah Malang, 2023)
Recent advances in artificial intelligence (AI) have led to the development of numerous successful applications that utilize data to significantly enhance the quality of life for people with visual impairment. AI technology has the potential to further improve the lives of visually impaired individuals. However, accurately measuring the development of visual aids continues to be challenging. As an AI model is trained on larger and more diverse datasets, its performance becomes increasingly robust and applicable to a variety of scenarios. In the field of visual impairment, deep learning techniques have emerged as a solution to previous challenges associated with AI models. In this article, we provide a comprehensive and up-to-date review of recent research on the development of AI-powered visual aides tailored to the requirements of individuals with visual impairment. We adopt the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, meticulously gathering and appraising pertinent literature culled from diverse databases. A rigorous selection process was undertaken, appraising articles against precise inclusion and exclusion criteria. Our meticulous search yielded a trove of 322 articles, and after diligent scrutiny, 12 studies were deemed suitable for inclusion in the ultimate analysis. The study's primary objective is to investigate the application of AI techniques to the creation of intelligent devices that aid visually impaired individuals in their daily lives. We identified a number of potential obstacles that researchers and developers in the field of visual impairment applications might encounter. In addition, opportunities for future research and advancements in AI-driven visual aides are discussed. This review seeks to provide valuable insights into the advancements, possibilities, and challenges in the development and implementation of AI technology for people with visual impairment. By examining the current state of the field and designating areas for future research, we expect to contribute to the ongoing progress of improving the lives of visually impaired individuals through the use of AI-powered visual aids.